It looks like nature - a phenomenological study of the built environment in psychotherapy from psychologists’ and psychiatrists’ perspective - Anne Hagerup; Helle Wijk; Göran Lindahl; Sepideh Olausson (International Journal of Qualitative Studies on Health & Well-Being)
Introduction The study aims to examine psychologists’ and psychiatrists’ experiences of built environments, indoors and outdoors, in providing psychotherapy. The research explores how the environment matters in clinical practice from the perspective of psychologists and psychiatrists and seeks to comprehend the significance of the facilities where psychotherapy takes place. Methods This study design is explorative and qualitative. Data is generated by eight in-depth interviews with six clinical psychologists and two psychiatrists and was analyzed using an interpretative phenomenological approach. Results Our findings revealed that the built environment matters in clinical practice as it appears to be closely linked to fostering a more comprehensive approach and facilitating various associations and themes in psychotherapy. Three superordinate themes emerged from the data: Design as therapeutic tool, Nature as a co-therapist, and lastly, Expanding the therapeutic space, highlights the participants’ perspective on the transformative potential of the built environment to become therapeutic. Conclusion The findings reveal how built environments can be actively utilized as tools in psychotherapy. Environments are not to be considered merely as neutral and passive spaces for conducting and receiving psychotherapy rather than experienced as places that may regulate and impact both therapists and patients, the relationship between them.